EVALUATION OF THE VALUE OF AMMONIA, NITRATE, AND NITRITE ON CULTIVATION MEDIA OF CATFISH FED MAGGOT - Larasati Putri Hapsari; Asep Suryana; Moch Nurhudah; Dzikri Wahyudi; Taufik Hadi Ramli (e-Jurnal Rekayasa dan Teknologi Budidaya Perairan, 2021)
Water quality is a limiting factor of life for aquatic biota, especially biota that lives in a pond. Therefore, water quality management is very necessary so that cultivation activities, especially ponds can continue and do not cause negative impacts on the surrounding environment. Various factors can decrease the water quality of aquaculture ponds one of which is from the remnants of feed and fish manure. Feed is one of the contributors to the dissolved organic matter in the cultivation pond. Maggot or black shoulder fly larvae are one of the alternatives that can be used as fish feed. Maggot has a high animal protein content of 30-45%, so it is very effective to be used as an alternative to additional feed in fish farming. The purpose of this research is to find out the difference in pond water quality between ponds by using maggot and pond feed by using pellet feed. The data taken in this study is primary data using the Complete Randomized Design (RAL) method with 3 treatments and 3 replays in each treatment. These treatments include Full Maggot Control (MU), 50% pellet, and 50% maggot (PU). Data obtained include; ammonia. Nitrites, and nitrates. The results showed that the average final value of ammonia, nitrite, and nitrates respectively treatment is KU ( 0.22 mg / L, 0.44 mg/L, 3.667 mg/L), PU (0.022 mg/L, 0.042 mg/L, 3.433 mg/L), MU (0.046 mg/L, 0.028 mg/L, 2.653 mg/L). The results illustrate the conclusion that the provision of maggots as an alternative and additional feed can improve the quality of aquaculture water.